ANALISA KONSUMSI MAKANAN KARIOGENIK TERHADAP ANGKA KEJADIAN KARIES PADA ANAK SEKOLAH DASAR DI KECAMATAN TEMBALANG KOTA SEMARANG - Ani Subekti; Erni Mardiati; Rizky Amalia Putri; Lutfi Asri ASri; Anggi Ratna Prahesti; Nisrina Nadyatin Nadyatin (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2020)
ABSTRACT Caries cases are mostly found at the age of development, namely elementary school children. The daily food consumed by school children at home and outside the home is a cariogenic food which is one of the causes of caries. The purpose of this study was to determine the incidence of caries rates that occur in elementary school age children and the dietary pattern of cariogenic food consumed by elementary school aged children in Semarang City.This type of research is analytic observational with a case control study approach. The sample was elementary school children in Tembalang Subdistrict, Semarang City as a group of cases with caries and non-caries as a control group. Cariogenic dietary variables were measured from the sugar content, frequency and consumption method using the Kariogenic Diet Survey. The data analysis used was the Chi-Square Test. Then proceed to test the causal factor analysis using the Odd Ratio.The results of the Odd Ratio showed that children who ate cariogenic foods with a high frequency had a higher caries rate than children who ate cariogenic foods less frequently. Based on the results of data analysis (correlation), it is known that caries and food frequency have a significance value of 0.004 0.05, which means that there is a significant correlation. Furthermore, between caries and food content the significance value is 0.030 0.05, which means that there is a significant correlation.The conclusion of this study is that there is a relationship between the frequency of cariogenic foods and the content of cariogenic foods on the incidence of caries. The higher the frequency of eating cariogenic foods, the higher the incidence of caries. Keywords : cariogenic food,, caries rate